Design and Construction of Modeling Tool of Linear Motion Experiment Assisted Toy Cars With Speed Control for Video Tracker Analysis - Firma Lestari; - Asrizal (PILLAR OF PHYSICS, 2022)
Experimental activities aim to improve understanding and thinking skills in understanding physics concepts. But in reality, the experiment has not been carried out properly, due to the use of manual instruments so it affects the results of the linear motion experiment obtained. As a solution to the problem, namely by making a linear motion experimental modeling tool assisted by a toy car with speed control for video tracker analysis. The purpose of this study is to determine the performance specifications of the linear motion experimental modeling tool, the accuracy and precision of the time measurement on the linear motion experimental modeling tool, to determine the effect of the relationship between physical quantities on the linear motion. The type of research conducted in engineering research. The data analysis technique used is descriptive data analysis and error analysis. From the data analysis, it can be stated three results of this research. First, the performance specifications of the linear motion experimental modeling tool consist of toy cars measuring 13x7 cm, controlling the dc motor using a step-down xl-6009 dc-dc, measuring angles using mpu6050, trajectory measuring 2.0x0.10 m, processing experimental results using tracking software. Second, the average accuracy of time measurement in LMCV is 98.16% with an average error of 1.93%. The average accuracy of time measurement in LMCV is 98.38% with an average error of 1.53%. Third, the velocity value obtained is proportional to the applied voltage value, while the acceleration value is proportional to the increase in the angle used.